Inducible secretion of IL-21 augments anti-tumor activity of piggyBac-manufactured chimeric antigen receptor T cells - Štach, Martin; Ptáčková, Pavlína; Mucha, Martin; Musil, Jan; Klener, Pavel; Otáhal, Pavel (Cytotherapy, 2020)
BACKGROUND: The efficiency of chimeric antigen receptor (CAR) T-cell-based therapies depends on a sufficient expansion of CAR T cells in vivo and can be weakened by intra-tumoral suppression of CAR T cell functions, leading to a failure of therapy. For example, certain B-cell malignancies such as chronic lymphocytic leukemia are weakly sensitive to treatment with CAR T cells. Co-expression of proinflamatory cytokines such as IL-12 and IL-18 by CAR T cells have been shown to enhance their antitumor function. We similarly engineered CAR T cell to co-express IL-21 and studied the effects of IL-21 on CAR T cells specific to CD19 and prostate-specific membrane antigens using an in vitro co-culture model and NSG mice transplanted with B-cell tumors. RESULTS: IL-21 enhanced the expansion of CAR T cells after antigenic stimulation, reduced the level of apoptosis of CAR T cells during co-culture with tumor cells and prevented differentiation of CAR T cells toward late memory phenotypes. In addition, induced secretion of IL-21 by CAR T cells promoted tumor infiltration by CD19-specific CAR (CAR19) T cells in NSG mice, resulting in reduced tumor growth. By co-culturing CAR19 T cells with bone-marrow fragments infiltrated with CLL cells we demonstrate that IL-21 reduces the immunosupressive activity of CLL cells against CAR19 T cells. CONCLUSIONS: CAR19 T cells armed with IL-21 exhibited enhanced antitumor functions. IL-21 promoted their proliferation and cytotoxicity against chronic lymphocytic leukemia (CLL). The results suggest that arming CAR T cells with IL-21 could boost the effectiveness of CAR T-mediated therapies.
Keywords: Humans; receptory antigenů T-buněk; T-Lymphocytes; interleukin-21; chronic lymphocytic leukemia; Phenotype; Interleukin-21; lidé; zvířata; proliferace buněk; myši; imunosupresivní léčba; Mice; piggyBac transposon; Receptors, Antigen, T-Cell; CAR T cells; interleukin 21; fenotyp; interleukiny; Cell Proliferation; Neoplasms; Immunosuppression Therapy; DNA Transposable Elements; nádory; Interleukins; T-lymfocyty; Animals; transpozibilní elementy DNA